1996
DOI: 10.1149/1.1837348
|View full text |Cite
|
Sign up to set email alerts
|

New Method of Purification of HF Chemicals for Very Large Scale Integration Manufacturing

Abstract: Metallic impurities having a lower ionization tendency than Si, such as Cu, are adsorbed onto the surface of the silicon substrate in hydrofluoric acid (HF) chemicals and buffered hycirofluoric acid (BHF) and then degrade device characteristics. A new purification method using a granular polysilicon (poly-Si) as an adsorbent was designed to remove the metallic impurities. As an adsorbent, Au deposited poly-Si (Au-poly-Si) was developed to improve the Cu removal efficiency of the poly-Si, and Au removed Au-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…7: a cumulative amount of 300 ppb corresponds to a bath concentration of 1.5 ppb). Equation 11can also be written as C [12] eq bSa where n,,10 is the total amount of impurity poured into the bath. This equation presents the advantage of highlighting the parameters affecting the impurity concentration in solution after purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7: a cumulative amount of 300 ppb corresponds to a bath concentration of 1.5 ppb). Equation 11can also be written as C [12] eq bSa where n,,10 is the total amount of impurity poured into the bath. This equation presents the advantage of highlighting the parameters affecting the impurity concentration in solution after purification.…”
Section: Resultsmentioning
confidence: 99%
“…Several purification techniques have already been applied to HF such as ion exchange,°1 reverse osmosis,1' and metal displacement. 12 Interesting results have been obtained with all of these techniques. However, there is still a lack of quantitative data to compare them.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al [11] showed that Cu impurities contained in spent VLSI HF solutions can be adsorbed in gold deposited granular poly-silicon adsorbents. Laboratory data show that working with 4.9% HF Cu level can be reduced from 50 ppb to less than 0.01 ppb (g/L).…”
Section: Introductionmentioning
confidence: 99%
“…12 Among these, PGMEA and PGME are predominantly used as solvents for photoresists and antireflective coatings. To purify these solvents, technologies such as ion exchange, 13 reactive distillation, 14 liquid−liquid extraction, 15 adsorption, 16 and membrane separation 17 are presently employed. Among these technologies, membrane-based separation was found to present fewer operational challenges.…”
mentioning
confidence: 99%